INDEPENDENT RESEARCHER OF REPUBLICAN SPIRITUALITY AND ENLIGHTENMENT CENTER - ABDULLAEVA XULKAR RAHMATULLAEVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paper work we can see consideration of the topic of knowledge is carried out in a special section of theoretical philosophy – epistemology. Philosophy, generalizing the experience of knowledge its own and scientific, formulates the most general principles of knowledge, thereby determining the strategy for implementing a persons cognitive attitude to the world and identifying prospects for transforming the world.